Citizenship status and arrest patterns in the United States: evidence from the arrestee drug abuse monitoring program - Kposowa, Augustine Joseph (Crime, law and social change, 2010)
The purpose of the study was to estimate associations between citizenship status and arrest for crimes among male arrestees. The primary hypothesis was that citizenship status (a rough proxy for immigration) has significant effects on arrest for violent personal crimes, property crimes, and four other selected offenses. Data were derived from the Arrestee Drug Abuse Monitoring (ADAM) Program for the years 2000 through 2002 inclusive. Our sample comprised male arrestees only. Logistic regression models were fitted to the data to estimate the citizenship status-crime relationship. Results showed no significant association between citizenship status and arrest for violent crimes. Non-citizens were 15% less likely than citizens to be arrested for property crimes; they were also less likely to be arrested for weapons offenses and drug offenses. Non-citizens were much less likely to test positive on NIDA-5 drugs than citizens. Non-citizens were, however, 50% more likely than citizens to be arrested for forgery/counterfeiting. It was concluded that public perceptions about the relationship of citizenship status to criminal behavior may be exaggerated and may not be borne out by empirical evidence. Limitations of the study are pointed out, including the fact that in the ADAM data, naturalized immigrants are lumped together with native born citizens.